2019
DOI: 10.1074/jbc.ra118.005087
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of collagen proteins in colorectal liver metastasis compared with normal liver tissue

Abstract: Edited by Xiao-Fan WangChanges to extracellular matrix (ECM) structures are linked to tumor cell proliferation and metastasis. We previously reported that naturally occurring peptides of collagen type I are elevated in urine of patients with colorectal liver metastasis (CRLM). In the present study, we took an MS-based proteomic approach to identify specific collagen types that are up-regulated in CRLM tissues compared with healthy, adjacent liver tissues from the same patients. We found that 19 of 22 collagen-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
77
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(82 citation statements)
references
References 43 publications
4
77
0
1
Order By: Relevance
“…In breast cancer, Ma et al () have shown upregulation of the gene expression of 23 collagen genes and that of 94 other ECM genes. Furthermore, Naba et al () and van Huizen et al () have shown that the collagen composition of colorectal liver metastasis is significantly different from that of healthy liver tissue.…”
Section: Structural and Functional Characteristics Of Collagenmentioning
confidence: 99%
See 1 more Smart Citation
“…In breast cancer, Ma et al () have shown upregulation of the gene expression of 23 collagen genes and that of 94 other ECM genes. Furthermore, Naba et al () and van Huizen et al () have shown that the collagen composition of colorectal liver metastasis is significantly different from that of healthy liver tissue.…”
Section: Structural and Functional Characteristics Of Collagenmentioning
confidence: 99%
“…A change in collagen turnover caused by external influences (eg, scurvy or fibrosis) also results in a diseased state. Collagen also plays a role in tumor development and metastasis (Fang et al, ; Xiong & Xu, ; van Huizen et al, ). For the reader interested in the role of collagen in fibrosis we recommend the review of Karsdal et al ().…”
Section: Introductionmentioning
confidence: 99%
“…There are three major isoforms of COL5, formed by the combination of three different polypeptide alpha chains (A1, A2, and A3), the collagen type V alpha 1 (COL5A1) homotrimer, the COL5A1/collagen type V alpha 2 (COL5A2)/collagen type V alpha 3 (COL5A3) heterotrimer, and the (COL5A1) 2 /COL5A2 heterotrimer which is the most functional . It was reported that certain polypeptide chains of certain type of collagen are highly abundant in certain cancer . Moreover, abnormal COL5 expression can promote tumor malignancy and progression in various types of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…3 It was reported that certain polypeptide chains of certain type of collagen are highly abundant in certain cancer. 4 Moreover, abnormal COL5 expression can promote tumor malignancy and progression in various types of cancer. However, its clinical role in TSCC is still not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…O colágeno tipo 1 é o mais abundante dentre os da família do colágeno, sendo formado por duas cadeias, alfa-1 (COL1A1) e alfa-2 (COL1A2)[90,91].A exata função desta proteína ainda não foi bem elucidada, porém apesar de grande parte dos estudos apontarem que proteínas colágeno estão hiper-regulada no CCR, podendo ser apontada por alguns como preditora de metástases hepática, o COL1A2 aparenta apresentar regulação negativa no CCR devido a hipermetilação do seu gene codificador. Um estudo realizado in vitro constatou que o COL1A2 inibe a progressão da neoplasia[57,[90][91][92].…”
unclassified